Genética de populações e inferências sobre a história demográfica de populações nativas sul-americanas - Marilia de Oliveira Scliar (2012)
ABSTRACTIn this study, we generated for the first time, resequencing data for 10 autosomal non-Coding regions (~ 20,000 bp) for 10 individuais of the Iarger Andean population, the Quechua, and for 10 individuais from the |\/Iachiguenga population (Shimaa Community) Iocated in the Selva Alta from Peru. This is a geographical region of transition between theAndes and Amazon, and therefore, we think that their populations could be good targets to elucidate possibie direotions of migration and settlement between the West and the East of the Continent.We used two Bayesian methods to infer the parameters of an isolation model with migration among Native American populations and among Native American and Asian populations. One of the methods is Iikelihood-based and uses Nlarkov Chain Monte Carlo simuiations to approximate the posterior probabiiity (INI program). The other, is the ABCmethod (Approximate Bayesian Computation, we on|y use this method for the isolation model with migration between Shimaa and Quechua populations) that instead of calculating the Iikelihood of a given model, it approximates the posterior probability by Comparing summary statistios estimated for the observed data with the Summary statistics Computed for Simuiated data on a particular modei (in this case the isolation model with migration). Our reSu|tS indioate a high diversity in the Quechua population, Cornparable with that of European populations, and a IittIe diversity in Shimaa, and this seems to be a subset of the diversity of Queohua. Additionally, we estimated that, when the divergence betweenShimaas and Oueohuas oocurred, 95% of the ancestral population gave rise to the Quechua, who remained until the present with a Iarge effective population size. We estimate a sma|| divergence time between the Queohua and Shimaa, you could Say Surprising, beoause the two populations are identified with two Completely different traditions, the Shimaas are associated with the Amazonian Culture, and the Ouechuas are associate with the Andean Cuiture. Our estimates among Asian and Native American popuiations Corroborate previous estimates using other genetic markers, Showing that Our population Quechua, in whichremains much Of the genetic variability of Native American populations, is an excellent population to study evolutionary processes Concerning not only to Andean populations, but also the entire popuiation of America.